In the fullness of time: an introduction to the biblical theology of Acts and Paul - Gaffin, Richard B. (Crossway, 2022)
"In this book, Richard B. Gaffin Jr. gives readers an accessible introduction to Acts and Paul. Building on a lifetime of study, Gaffin teaches on topics including the redemptive-historical significance of Pentecost; eschatology; and the fulfillment of redemptive history in the death and resurrection of Christ. In the Fullness of Time is an exegetical "textbook" for pastors, students, and lay leaders seeking to learn more about Acts and Paul from a Reformed and evangelical perspective"--